2001
DOI: 10.1002/jsfa.972
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and ruminal degradability of lucerne (Medicago sativa) products

Abstract: A study was conducted to determine the chemical composition and in situ nutrient ruminal degradability of three lucerne products. These were dehydrated pellets, sun-cured pellets and cubes. Results of the chemical analysis showed that sun-cured pellets had the highest (P < 0.05) neutral and acid detergent ®bre as well as total carbohydrate levels, followed by cubes and dehydrated pellets respectively. Crude protein (CP) content was highest (P < 0.05) for dehydrated pellets (204.3 g kg ). Intermediately degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…All species in this study contained low levels of rapidly degradable TP fraction (B1) (average of 8 % of the TP). The CP and TP fraction values for alfalfa are in good agreement with those reported in the literature, and indicate that intermediately degradable protein is the main protein fraction in this species (Lintzenich et al. 1995, NRC 1996, 2001, Mustafa et al.…”
Section: Resultssupporting
confidence: 88%
“…All species in this study contained low levels of rapidly degradable TP fraction (B1) (average of 8 % of the TP). The CP and TP fraction values for alfalfa are in good agreement with those reported in the literature, and indicate that intermediately degradable protein is the main protein fraction in this species (Lintzenich et al. 1995, NRC 1996, 2001, Mustafa et al.…”
Section: Resultssupporting
confidence: 88%
“…High levels of rapidly degradable carbohydrates have also been reported for other forages. 27 Total digestible nutrients concentrations were similar for the cactus varieties and averaged 667 g kg −1 . Based on NRC 8 values, the TDN (Total digestive nutrient) values of cactus may be equivalent to that of good quality alfalfa hay.…”
Section: Results and Discussion Chemical Composition Of Cactimentioning
confidence: 90%
“…However, values of true protein fractions reported in this study for cacti are similar to those reported for other forages, such as alfalfa products. 27 Mineral analysis showed that cactus varieties contained high calcium (Ca) and magnesium and low phosphorus (P) and copper concentrations ( Table 3). The Miúda variety contained higher (P < 0.05) Ca and lower (P < 0.05) manganese levels than the other two varieties.…”
Section: Results and Discussion Chemical Composition Of Cactimentioning
confidence: 99%
“…Lucerne is mainly used to make hay and silage, but can also be used for grazing purposes, because of its high yield, quality and wide adaptability to different climates and soil types (NLO, 2010). Lucerne may be grown as a cover crop and often increases yield of succeeding crops such as potatoes, rice, cucumber, lettuce and tomatoes (Mustafa et al , 2001).…”
Section: Introductionmentioning
confidence: 99%